Identifikasi Mikroplastik Polypropylene (PP) Menggunakan Metode Wet Peroxide Oxidation (WPO) - Afriyani, Ratih; Dewata, Indang (Departemen Kimia FMIPA UNP, 2024)
Microplastics are plastic waste smaller than 5 mm. The small size of microplastics raises concerns for living creatures because microplastics are very dangerous and widespread in the environment. Polypropylene (PP) microplastics are the most widely used synthetic microplastics. This research was carried out with the aim of finding out the optimum conditions for a method for identifying PP microplastics from waters. This method is Wet Peroxide Oxidation (WPO) because conceptually it is cheaper and simpler. In this research, stages of optimizing oven and heating times and H2O2 concentrations will be carried out to obtain optimal microplastic identification results. Identification uses a stereo microscope to see the shape and color of microplastics, determine the chemical composition from the spectrum which is measured using Fourier Transform Infrared (FTIR) and analyze the material composition and determine the composition of all types of chemicals from plastic particles using X-Ray Fluorescence (XRF). The results of microplastic separation using this method were optimal at an oven time of 18 hours, H2O2 concentration of 30% and heating time of 35 minutes. The results of identification using a microscope showed that the identified microplastics were fragment type microplastics, the colors of the microplastics were transparent and black. The characteristics of functional groups using FTIR show the optimum loss of impurities in the sample. For the XRF test there are additives and heavy metals absorbed from the environment.